The “Let’s Talk about Children” intervention in a Finnish school context: fidelity, parents’ experiences, and perceived benefits - Allemand, Lotta; Niemelä, Mika; Merikukka, Marko; Salmela-Aro, Katariina (Frontiers in Psychology, 2023)
The Let’s Talk about Children intervention is a tool for parents and professionals to work together to promote children’s positive development, resilience, and psychosocial well-being in social and healthcare services, at school, and in day care. The aim of this study was to evaluate the fidelity, parents’ experiences, and perceived benefits of using the Let’s Talk about Children intervention in a school context. Participants (N=65 first-grader parents) completed an online questionnaire after the intervention. The results show that the intervention was delivered as designed and conducted with high fidelity. Parents’ experiences of the Let’s Talk about Children discussions were positive, parents felt that the atmosphere was good during the discussion, and the participants reported benefits from the intervention. The trial has been registered in the ClinicalTrials.gov registry (NCT05038280).